Outbreak preparedness and response strategies in ASEAN member states: a scoping review - Fingani Annie Mphande; Nan Jiun Yap; Chin Hai Teo; Li‐Yen Chang; Sun Tee Tay (IJID Regions, 2024)
Objectives: century has witnessed significant disease outbreaks with severe impact in Association of Southeast Asian Nations (ASEAN) countries, including SARS, H1N1, H5N1, and COVID-19. This review aimed to compile and analyze outbreak preparedness and response strategies, highlighting the success of coordinated multi-sectoral approaches and policy responses within the ASEAN region. Methods: The protocol for this review was registered on the Open Science Framework and PROSPERO. A systematic analysis of publications from the 2002-2022 period was conducted following PRISMA guidelines on 4522 records retrieved from PubMed, CINAHL, Web of Science, and Scopus. The titles and abstracts were screened, and 229 articles were selected for full-text screening. Finally, 34 articles were included in this review. Results: Four preparedness pillars were identified: governance and stewardship, disease detection, disease prevention, and health care management. The pillars were crucial in preparing for and responding to the COVID-19 pandemic. Coordinated responses among the ASEAN countries and local and international stakeholders were reported. Conclusions: The findings emphasize that understanding the transmission dynamics of infectious diseases is paramount for effective disease prevention, surveillance, and timely response efforts to prevent the next pandemic. A well-coordinated multi-country and multi-agency policy response and understanding the different disease management models are crucial in addressing future outbreaks in the region. Future post-pandemic publications will shed more light on lessons learned and preparedness and response plans for future pandemics.
Keywords: COVID-19 epidemiological studies; Viral Infections and Outbreaks Research; Zoonotic diseases and public health